2013
DOI: 10.1590/s1415-52732013000500008
|View full text |Cite
|
Sign up to set email alerts
|

Jaboticaba (Myrciaria jaboticaba (Vell.) Berg.) peel improved triglycerides excretion and hepatic lipid peroxidation in high-fat-fed rats

Abstract: ERRATANo artigo "Jaboticaba (Myrciaria jaboticaba (Vell.) Berg.) peel improved triglycerides excretion and hepatic lipid peroxidation in high-fat-fed rats" publicado no número 5, volume 26, Revista de Nutrição, na página 571, onde se lê:"Jaboticaba (Myrciaria jaboticaba (Vell.) Berg.) peel increased triglycerides excretion and hepatic lipid peroxidation in high-fat-fed rats" Leia-se:"Jaboticaba (Myrciaria jaboticaba (Vell.) Berg.) peel improved triglycerides excretion and hepatic lipid peroxidation in high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, Batista et al (2013), evaluating the effect of jabuticaba peel [ Myrciaria jaboticaba (Vell.) Berg.]…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Batista et al (2013), evaluating the effect of jabuticaba peel [ Myrciaria jaboticaba (Vell.) Berg.]…”
Section: Resultsmentioning
confidence: 99%
“…Jabuticaba peel has been identified as a potential source of bioactive compounds with biological activities. In vivo studies were performed by Batista et al [141], who obtained an improvement in the triglyceride excretion and hepatic lipid peroxidation in rats fed a high-fat diet enriched with lyophilized jabuticaba peel. Palozi et al [142] showed that the oral use of ethanolic extracts of jabuticaba peel in rabbits did not cause significant changes in respiratory, cardiovascular, and central nervous system functions, ensuring pharmacological safety for the use of this residue.…”
Section: Fruit By-products (Seeds): Chemical Characterization and mentioning
confidence: 99%
“…According to Batista et al [ 38 ], consumption of jabuticaba peel can contribute to the improvement of gastrointestinal tract functioning and can protect the liver against the action of certain free radicals, due to the abundance of fiber and antioxidant compounds, such as flavonoids. In this scenario, the exploration of the bioactive and technological potential of jabuticaba is extremely important and becomes a promising alternative product, aimed at the development of food and/or drugs and the reduction, at an environmental level, of the waste generated in the industrialization of these fruits.…”
Section: Introductionmentioning
confidence: 99%